The Implementation of Ki Hadjar Dewantara's Leadership in the Strengthening of the Pancasila Student Profile Project at SMP Negeri 3 Marioriwawo, Soppeng Regency - Asmar, Asmar; Ansar, Ansar; Pada, Amir (International Journal of Education, Information Technology, and Others, 2025)
This study is motivated by the challenges faced by some teachers in implementing the Pancasila Student Profile Strengthening Project at SMPN 3 Marioriwawo, Soppeng Regency. The study aims to describe the implementation of Ki Hadjar Dewantara's leadership principles in teaching. The research method used is qualitative, with data collection techniques including interviews, observations, and documentation. Data analysis is conducted through three stages: data reduction, data presentation, and verification, while data validity is ensured using source and method triangulation techniques. The findings indicate that in the implementation of Ing Ngarsa Sung Tuladha (leading by example), the principal and teachers identify students’ needs by designing diagnostic assessments and consistently instilling discipline through the enforcement of a code of ethics. In the implementation of Ing Madya Mangun Karso (inspiring in the middle), the principal forms an implementation team through discussions with teachers, collaborates with parents and external parties, motivates students using prompting questions, conducts field surveys, and facilitates learning resources tailored to students' interests. For Tut Wuri Handayani (supporting from behind), teachers organize open discussions, brainstorming sessions, and provide opportunities for students to present their ideas while giving constructive feedback. Additionally, the principal conducts regular observations. This research is expected to provide insights into leadership and educational practices in schools, as well as support the development of character and Pancasila values among students.